Transparansi Pemerintahan Desa Dalam Pengelolaan Dana Desa Tahun 2018 (Studi Kasus Desa Talang Kering Kecamatan Air Napal Kabupaten Bengkulu Utara) - Tri Purwanti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to find out how Transparency of Village Government in Village Fund Management in 2018 in Talang Kering Village, Air Napal District, North Bengkulu Regency. This study uses a descriptive research method with a qualitative approach. The results of the study were obtained by conducting interviews, observation and documentation obtained based on the aspects of this study, namely looking into the process of planning, implementation and accountability of Village Fund management based on government budget transparency indicators (Kristianten, 2006: 73), namely availability and accessibility of documents, provision of information clear about procedures and costs, ease of access to information and the existence of a regulatory framework that guarantees openness. The results of this study found that, the Talang Kering village government has implemented transparency in managing village funds in accordance with the laws and regulations by providing easy access to Village Fund management documents and delivering information related to Village Fund management to the community either orally or in writing, in the form of socialization or information media such as baleho, bulletin boards and newspapers.